Overview of World ATW (Air to Water) Heat Pump Market and Opportunities with Respect to the Air-Conditioning Industry - Shukla, Kedar; Jadeja, Jayrajsinh; Trivedi, Hemant (Prabandhan: Indian Journal of Management, 2015)
A heat pump is a device that transfers heat energy from a heat source to a heat sink against a temperature gradient. Heat pumps are designed to move thermal energy opposite to the direction of spontaneous heat flow. A heat pump uses some amount of external high-grade energy to accomplish the desired transfer of thermal energy from heat source to a heat sink. While compressor-driven air conditioners and freezers are familiar examples of heat pumps, the term "heat pump" is more general and applies to Heating Ventilation and Air Conditioning (HVAC, hereafter) devices used for space heating or space cooling. When a heat pump is used for heating, it employs the same basic refrigeration-type cycle used by an air conditioner or a refrigerator but in the opposite direction, releasing heat into the conditioned space rather than the surrounding environment. There are two types of heat pump technology, geothermal and aerothermal. Geothermal types include ground to water and water to water type heatpumps, while aerothermal heatpump technology is broadly used by the air-conditioning industry. Among the two types of aerothermal heat pumps, these are (a) Air to Air (ATA) and (b) Air to Water (ATW). Though ATA heat pumps were widely used so far in the air-conditioning industry, predominantly, there is a sudden and significant growth observed in the ATW heat pump market due to their energy efficient performance; and hence, the market is observing a technology shift. The present paper attempted to study the market segmentation of the heat pump industry with special focus on technical detailing and applications of ATW heat pumps. The research paper further described the key competitive players competing in the world market of ATW heat pump business. Secondary data analysis and review of global market for the last one decade (2004 to 2012) was carried out with a focus on leading countries or subcontinents' performance like that of Japan, China , Europe, Australia, United States, and some other small markets to draw the 'opportunities and challenges' roadmap for the ATW heat pump industry.